Between Individual and Collective Actions: The Introduction of Innovations in the Social World of Climbing - Kacperczyk, Anna (Qualitative Sociology Review, 2019)
This article, which is based upon the findings of a seven-year research project concerning the social world of climbing, discusses climbing as an organized social practice that possesses a strong historical dimension and collective character. It examines the relation between individual participants and that social world as a whole, and it accepts that an individual’s personal life may be inscribed in the development and formation of that world in two ways. These are 1) a given social world imposes the behavioral patterns, normative rules, institutional schemes of actions, and careers upon participants that characterize their identities and actions; and 2) the actions of an individual participant trigger significant change in that world. I am particularly interested in those unique situations in which when a participant induces a change that affects a given social world (or a sub-world) as a whole, and discuss two examples of this relation, namely, the history of designing and creating climbing equipment, and setting new standards of climbing performance. Briefly stated, innovative solutions are born in conjunction with particular climbing actions that are either promoted or hindered depending on whether or not the vision of the primary activity associated with those solutions was accepted by the majority of participants. The dynamics and transformations of the social world in question thus rely upon the activities of exceptional individuals who, as pioneers, innovators, and visionaries, attain mastery in performing the primary activity of that world and set new standards of performance for others. A new mode of acting—in order to be collectively adopted—must be accepted as both valuable and morally justified by all participants.